Economic Evaluation of Combination Therapy Versus Monotherapy for Treatment of Benign Prostatic Hyperplasia in Hong Kong - Wu, David Bin-Chia; Yee, Chi Hang; Ng, Chi-Fai; Lee, Shaun Wen Huey; Chaiyakunapruk, Nathorn; Chang, Yu-Shan; Lee, Kenneth Kwing Chin (Frontiers in Pharmacology, 2018)
Background: Lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH) is a common condition affecting men. Studies have shown that the prevalence of LUTS/BPH increases with age, which will cause considerable economic burden to the healthcare system and society. The aim of the present study was to evaluate the long term cost effectiveness of dutasteride and tamsulosin therapy compared to tamsulosin alone in men with BPH in Hong Kong. Methods: A Markov decision model was constructed to estimate the economic impact from a healthcare payers’ perspective, which only included direct costs. Analyses were conducted for a 4-year time frame. Results: When compared to tamsulosin alone, combination therapy was more expensive but also more effective in preventing complications and reduced the need for surgery. Over life-time projection suggest that combination therapy will be cost-effective if the willingness-to pay threshold of USD20,000. Conclusion: Findings of this study found that combination therapy of tamsulosin and dutasteride was more cost-effective compared to tamsulosin alone across a wide range of scenario.